Contemporary predicament of Asian American studies toward a radical critique - San Juan, Epifanio, Jr (Danyag :the UPV journal of humanities and social sciences, 2009)
"The onset of global capitalism's crisis has exposed the fragile theoretical underpinnings of Asian American Studies as an academic discipline. Spellbound by deconstructive, rhetorical assumptions, all symptomatic of commodity fetishism and alienation, mainstream Asian American critics continue to validate neoliberal pluralism while claiming to value difference and singularity. While rejecting U.S. exceptionalism, they ignore historical specifiicities and endorse individualist norms, affects, genealogical plurality, and performative discourses of the de-centered subject all uncritical of free-market reification. What is needed is a return to a mode of critical inventory that takes account of historical capitalist, imperialist geopolitics, and the notion of collective agency necessary to destroy racialized ideological practices and institutions that maintain the exploitative capitalist division of labor, social injustice, and inequality of peoples based on private appropriation of social wealth."